Historical background of arab achievements in the islamic golden age - Mohammed, Ali Haj (2012)
This paper aims to identify the Arab achievements during the Islamic Golden Age. It identifies the major inventions and creations, particularly in the field of Science, and their influence on the rest of the world, most specifically the West. It also comments on the issue of the consequences of the Arab invasion of Europe and the creation of network trading between East and West. Finally, it deals with the challenges in the Arab world today, underlining lack of proper use of resources as main obstacles for attracting investors. ---- Esta contribuição visa identificar as realizações dos Árabes durante a Idade de Ouro Islâmica. Identifica as principais invenções e criações, especificamente no campo da Ciência, e a sua influência no resto do mundo — mais especificamente no Ocidente. Para além disso, comenta sobre o tema das consequências das invasões árabes na Europa e a criação de redes comerciais entre o Leste e o Oeste. Finalmente, a contribuição aponta os desafios do mundo árabe de hoje, salientando a falta de recursos como principal obstáculo para atrair investidores.